The Rural Economy and the British Countryside (London Earthscan, 2009)
Mention of the British countryside commonly evokes visions of pastoral contentment; but the nature of rural Britain has changed dramatically since 1945. The declining importance of farming as a source of income and employment in the course of this century has undermined the simple identity of the rural economy with the agricultural sector. The social composition of many villages has been transformed by incomers who commute to nearby towns and cities for their work. And EU policy is playing an increasingly important role in both the regulation of the countryside and the promotion of development through structural assistance programmes. The Rural Economy and the British Countryside offers critical perspectives on the changing profile of rural Britain by leading contributors in the field. It considers the meaning of the term 'rural' and what might constitute a sustainable rural economy; present and future patterns of rural development; the role of markets; natural resource management; agricultural pollution; marketing policies in the agricultural sector; environmental valuation techniques; rural policies and politics; and the future of the rural political economy. Written by a team of experts at the Centre for Rural Economy, which took a leading role in the debate surrounding preparation of the 1995 Rural White Paper, the book is ideal for students of rural and environmental policy, countryside management, planning and recreation, rural geography, and agriculture and environmental studies courses. Paul Allanson is a Lecturer in Economics at the University of Dundee, specialising in evolutionary economics and structural change in agriculture. Martin Whitby is Professor of Countryside Management at the University of Newcastle upon Tyne, and is the author of Incentives for Countryside Management: the Case of ESAs and the European Environment and CAP Reform, among other titles. Originally published in 1996
Includes index
Keywords: Rural economy